2019
DOI: 10.1038/s41598-018-36897-w
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluating analgesic efficacy and administration route following craniotomy in mice using the grimace scale

Abstract: Most research laboratories abide by guidelines and mandates set by their research institution regarding the administration of analgesics to control pain during the postoperative period. Unfortunately, measuring pain originating from the head is difficult, making adequate decisions regarding pain control following stereotaxic surgery problematic. In addition, most postsurgical analgesia protocols require multiple injections over several days, which may cause stress and distress during a critical recovery period… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 27 publications
0
36
0
Order By: Relevance
“…Furthermore, the rat strain used may have impacted on the ability to accurately score facial features. Previous research has implied that detection of grimace facial features in dark-colored animals is impaired [33,34]. This may however be as a result of poor achievement of background contrast, rather than the pigmentation of the animal per se.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the rat strain used may have impacted on the ability to accurately score facial features. Previous research has implied that detection of grimace facial features in dark-colored animals is impaired [33,34]. This may however be as a result of poor achievement of background contrast, rather than the pigmentation of the animal per se.…”
Section: Discussionmentioning
confidence: 99%
“…These differences that are observed in group-housed male mice are likely not reflective of higher mammalian disease models. Previous studies demonstrated differences between males and females with regard to pain and analgesia, but these data vary based upon species of animal, pain model used, and type of analgesic administered [130][131][132][133][134][135][136][137][138][139][140][141]. Thus, sex differences can also be confounding variables when examining pain and analgesia as well.…”
Section: Discussionmentioning
confidence: 99%
“…DeepLabCut is an open-source animal tracking program that uses deep neural networks to recognize labelled points in videos. 16 DeepLabCut’s tracking algorithm was trained to recognize the mouse’s centre, labelled as visually close to EthoVision’s calculated centre as possible, with 200 distinct marked reference frames. All other settings were left as default as specified in the setup protocol.…”
Section: Methodsmentioning
confidence: 99%
“…These concerns have led to increased usage of unconditioned or non-evoked behavioral responses with the aim of capturing endogenous indicators of spontaneous or ongoing pain. 11 Such measures include operant assays, the Mouse Grimace Scale, 16 , 17 automated behavioral tracking, 11 weight-bearing or gait analysis, nesting or burrowing behavior, ultrasonic vocalizations, and free-choice temperature preference. 18 , 19 Along with increased adoption of assays for spontaneous pain, there has also been an increase in the automation of data collection.…”
Section: Introductionmentioning
confidence: 99%